A randomized controlled trial of methotrexate for patients with generalized myasthenia gravis. (5th July 2016) - Pasnoor, Mamatha; He, Jianghua; Herbelin, Laura; Burns, Ted M.; Nations, Sharon; Bril, Vera; Wang, Annabel K.; Elsheikh, Bakri H.; Kissel, John T.; Saperstein, David; Shaibani, J. Aziz; Jackson, Carlayne; et al.
Abstract : Objective: To determine the steroid-sparing effect of methotrexate (MTX) in patients with symptomatic generalized myasthenia gravis (MG). Methods: We performed a 12-month multicenter, randomized, double-blind, placebo-controlled trial of MTX 20 mg orally every week vs placebo in 50 acetylcholine receptor antibody–positive patients with MG between April 2009 and August 2014. The primary outcome measure was the prednisone area under the dose-time curve (AUDTC) from months 4 to 12. Secondary outcome measures included 12-month changes of the Quantitative Myasthenia Gravis Score, the Myasthenia Gravis Composite Score, Manual Muscle Testing, the Myasthenia Gravis Quality of Life, and the Myasthenia Gravis Activities of Daily Living. Results: Fifty-eight patients were screened and 50 enrolled. MTX did not reduce the month 4–12 prednisone AUDTC when compared to placebo (difference MTX − placebo: −488.0 mg, 95% confidence interval −2, 443.4 to 1, 467.3, p = 0.26); however, the average daily prednisone dose decreased in both groups. MTX did not improve secondary measures of MG compared to placebo over 12 months. Eight participants withdrew during the course of the study (1 MTX, 7 placebo). There were no serious MTX-related adverse events. The most common adverse event was nonspecific pain (19%). Conclusions: We found no steroid-sparing benefit of MTX in MG over 12 months of treatment, despite being well-tolerated. This study demonstrates the challenges of conducting clinical trials in MG, including difficulties with recruitment, participants improving on prednisone alone, and the need for a better understanding of outcome measure variability for future clinical trials. Classification of evidence: This study provides Class I evidence that for patients with generalized MG MTX does not significantly reduce the prednisone AUDTC over 12 months of therapy.